2010
DOI: 10.1002/adsc.201000517
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Bromine‐Lithium Exchange: A New Tool to Build Axial Chirality

Abstract: We present here the first catalytic desymmetrization of the 2,2',6,6'-tetrabromobiphenyl 1 and analogues, by a bromine-lithium exchange catalyzed by either diamines or diether derivatives (0.5 equiv.), yielding axially chiral compounds in high yield (up to 89%) and high enantioselectivity (up to 82%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 39 publications
(21 reference statements)
0
26
0
Order By: Relevance
“…[3] Strategies which have been developed recently include the use of dynamic kinetic resolution [4] and dy-namic thermodynamic resolution, [5] resolutions based on sulfoxide chemistry, [5,6] and atropselective transition-metal-catalysed coupling. [7] Enzymatic desymmetrisation is an appealing method for asymmetric synthesis, [8,9] but it is noteworthy that only three examples of enzymatic desymmetrisation applied to atropisomers have been reported, [9][10][11] and only two of these involve the most common class of atropisomers, the biaryls. [9] We now report that simple symmetrical biaryls may be desymmetrised by a rapid enantioselective oxidation catalysed by a variant of galactose oxidase (GOase M 3-5 ) developed in our group previously, [12] or alternatively (and complementarily) by enantioselective reduction by using a panel of ketoreductases (KREDs).…”
mentioning
confidence: 99%
“…[3] Strategies which have been developed recently include the use of dynamic kinetic resolution [4] and dy-namic thermodynamic resolution, [5] resolutions based on sulfoxide chemistry, [5,6] and atropselective transition-metal-catalysed coupling. [7] Enzymatic desymmetrisation is an appealing method for asymmetric synthesis, [8,9] but it is noteworthy that only three examples of enzymatic desymmetrisation applied to atropisomers have been reported, [9][10][11] and only two of these involve the most common class of atropisomers, the biaryls. [9] We now report that simple symmetrical biaryls may be desymmetrised by a rapid enantioselective oxidation catalysed by a variant of galactose oxidase (GOase M 3-5 ) developed in our group previously, [12] or alternatively (and complementarily) by enantioselective reduction by using a panel of ketoreductases (KREDs).…”
mentioning
confidence: 99%
“…The syntheses of tetraphosphanes 1 starting from 3 requires two consecutive halogen/lithium exchange and electrophilic reaction with chlorophosphanes (Scheme 2) [2,5,7,8,30]. The first conversion of 3 to the dibromo biphenyls 4aec usually proceeds with no complications and yields the desired compounds 4 as the main product.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is not manifest in the achiral halogen-Li exchange, where 1 equivalent of n-BuLi is used in Et 2 O, whereas 2 equivalents of t-BuLi are used in either Et 2 O or THF. 1, 2 s-BuLi and ArLi are rarely used in this routine 7 In the couse of our studies, it was found that when using n-BuLi for the Br-Li exchange, at low temperature in an apolar solvent, such as toluene, a Lewis base was required. 11 In contrast, we found that s-BuLi allows an efficient Br-Li exchange even in the absence of a Lewis base.…”
mentioning
confidence: 86%
“…In the beginning, moderate enantioselectivities were obtained with chiral diamines such as (-)-sparteine (L1). 6b In 2010, 7 we reported a catalytic version using Tomioka's chiral 1,2-diether L7 8 for the preparation of biaryl atropoisomers with an enantiomeric excess of up to 82%. The desymmetrisation of prochiral biaryl polyhalides is a topic of intense interest as a key reaction giving access to a family of widely used chiral ligands such as BINAP, BIPHEMP, MeO-BIPHEP.…”
mentioning
confidence: 99%